Implementation of Total Productive Maintenance (TPM) for Boiler Machines at PT. KPBN Belawan - Herbin Efendi Hutabarat; Vidi Agung Fragastia; Syahputra Amri (LPPM Universitas Potensi Utama, 2025)
The main problem faced by PT. KPBN Belawan is the low level of efficiency of boiler machines due to the lack of scheduled and systematic maintenance. Currently, the applicable maintenance system is preventive and corrective, which is ineffective due to the lack of attention from management and machine operators. Therefore, it is important to introduce a more effective and efficient maintenance system to maintain the performance of these machines. One approach that can be adopted is Total Productive Maintenance (TPM), which offers a more comprehensive maintenance strategy compared to other methods. By focusing on employee involvement, reducing downtime, cost efficiency, improving machine quality, increasing machine life, and improving workplace safety, TPM emerges as a very relevant and effective strategy to improve operational performance in the tank storage industry. This study aims to propose the implementation of Total Productive Maintenance (TPM) on boiler machines to overcome various problems faced by companies that utilize boiler machines in their production processes. To analyze the problem, the observer will assess the extent of the change in the effectiveness of the boiler machine operation and perform the following calculations: Overall Equipment Effectiveness (OEE) analysis, OEE Six Big Losses analysis, and Pareto Diagram analysis. Based on the results of the study, the following conclusions can be drawn: Activities carried out on the boiler machine at PT. KPBN Belawan has produced an Overall Equipment Effectiveness (OEE) value of 68.31% from May to October 2024, which is still below the standard threshold. From this study, several recommendations are proposed for the company: 1. Continuous calculation of Overall Equipment Effectiveness (OEE) for production machines and equipment is needed to obtain the latest information for planning continuous machine repairs as an effort to increase production efficiency at PT. KPBN Belawan. 2. Measuring the effectiveness of the boiler machine using the OEE method requires further assessment and calculation to determine which of the Six Big Losses most significantly affects the decline in the effectiveness of the boiler machine.